Light emitting diode based on boron-nitrogen-fluorine co-doped carbon dots and preparation method thereof

The existing heavy metal preparation was solved by using blue fluorescent carbon dot powder prepared based on boron-nitrogen fluorine co-doped carbon dots (BNF-CDs) in the light-emitting diode, combined with poly9-vinyl carbazole (PVK) as the main material. The problems of high toxicity and low stability of light emitting diodes have achieved high efficiency light emitting diode devices.

CN119486476APending Publication Date: 2025-02-18SHANTOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411656772.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing light emitting diodes prepared based on heavy metals have problems such as high toxicity, low stability and high cost, and it is difficult to further develop in the lighting and display market.

Method used

Using boron-nitrogen fluorine-codoped carbon dots (BNF-CDs) as the luminescent material, using 4-fluorophenylboric acid and m-phenylenediamine as the precursor in organic solvents, and preparing blue fluorescent carbon dot powders through solvothermal reactions BNF-CDs and combined with poly9-vinyl carbazole (PVK) as the host material is used in the luminescent layer.

Benefits of technology

It has achieved high efficiency light emitting diodes, with an external quantum efficiency (EQE) of 4.98%. It is currently the CLED with higher device efficiency among carbon dot-based light emitting diodes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119486476A_ABST
    Figure CN119486476A_ABST
Patent Text Reader

Abstract

The invention discloses a light-emitting diode based on boron-nitrogen-fluorine co-doped carbon dots and a preparation method thereof, and belongs to the technical field of luminescent materials, specifically, 4-fluorophenylboronic acid is used as a first precursor, m-phenylenediamine is used as a second precursor, and a series of blue carbon dot fluorescent powder BNF-CDs can be prepared through reaction under different molar ratios. And preparing a light-emitting layer mixed solution by taking the BNF-CDs with the highest fluorescence quantum yield as a guest material, poly (9-vinylcarbazole) (PVK) as a host material and o-dichlorobenzene as a solvent, and preparing the light-emitting diode with excellent structural stability and high efficiency by taking the light-emitting layer mixed solution as a light-emitting layer raw material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of luminescent materials, and in particular relates to a light emitting diode based on boron, nitrogen and fluorine co-doped carbon dots and a preparation method thereof. Background Art

[0002] With the advent of the era of informatization and globalization, people's lifestyles have led to the rapid development of light-emitting diodes (LEDs). In the current consumer electronics market, light-emitting diodes have better color contrast, wider color space and higher current luminous efficiency than traditional liquid crystal displays. The emergence of LEDs is considered a revolutionary innovation in the field of lighting sources and full-color displays. Organic light-emitting diodes (OLEDs), a new generation of flat-panel display technology, bring more diverse display application scenarios due to their self-luminescence, short response time, high luminous efficiency, wide viewing angle, wide color gamut, light weight and good flexibility. However, problems such as insufficient color saturation and poor stability make it difficult for OLED to develop further in the field of display and lighting. In recent years, with the rapid development of the display and lighting fields, light-emitting diodes (QLEDs) prepared based on quantum dots have attracted widespread attention from researchers around the world. QLEDs have been widely used in the display and lighting fields due to their unique advantages such as adjustable photoluminescence, bright brightness, simple solution processing capabilities and high color saturation. Compared with OLED, QLED has unique advantages, such as better color saturation and simpler preparation conditions. Unfortunately, heavy metal-based (such as Cd 2+ and Pb 2+ ) prepared by QLEDs, its high toxicity, low stability and high cost are difficult to avoid. These thorny problems seriously hinder their further development and practical use in the lighting and display markets. Therefore, the development of new luminescent materials with low or even non-toxicity, good stability, brightness and simple preparation, and their application in LED devices has become an urgent problem that needs to be solved. Taking advantage of the high stability, low cost, environmental friendliness, non-toxicity and pollution-free of carbon materials, efficient carbon-based luminescent materials not only enhance the prospects of the next generation of carbon photonic and optoelectronic technology frontiers, but also provide a new possibility for the lighting and display fields. Carbon dots (Carbon Dots, CDs) have attracted great attention in optoelectronic devices, especially electroluminescent LEDs. Therefore, carbon-based light-emitting diodes (Carbon Dots Light-Emitting Diodes, CDLEDs) prepared based on carbon dots have attracted much attention.

[0003] In practical applications, the white light of light-emitting diodes is mainly composed of three primary colors, and the three luminescent materials corresponding to the three primary colors, blue, green, and red, are the basis for realizing high color rendering index lighting applications and wide color gamut display applications. At present, the development trend of green and red light in the market is better than that of blue light (thanks to phosphorescent materials), which can meet the needs of commercialization. The development of blue light materials is relatively lagging, which is mainly due to the inherent contradiction between optics and electricity. Therefore, in order to be able to meet the requirements of high efficiency and high color purity at the same time, the research and development of blue light materials is still quite challenging. In addition, blue light LEDs are the key factor in realizing display and lighting in all saturated spectral emissions, and are also the cornerstone of generating saturated white light in LED technology applications. How to develop cost-effective, environmentally friendly, low-toxic, and efficient luminescent materials and construct blue light-emitting diodes is still a huge challenge.

[0004] The performance of CDLED devices needs to be evaluated from two aspects: optical performance and electrical performance. This mainly includes external quantum efficiency (EQE), power efficiency (PE, lmW -1 )、Starting voltage (V on , V), maximum luminous brightness (L max , cd m -2 ), Color Index Coordinates (CIE), Efficiency Roll-off, Current Efficiency (CE, cdA -1 )wait.

[0005] Among them, the external quantum efficiency is the ratio of the number of photons emitted by the device to the number of injected carriers, and its calculation formula is:

[0006] EQEmax=ηr×γ×ΦPL×ηout

[0007] Among them, γ is the carrier recombination ratio. In an ideal situation, carrier injection and transmission are balanced, and the carrier recombination ratio is 100%; ηr is the exciton utilization rate; ΦPL is the photoluminescence efficiency, that is, the fluorescence quantum yield of the luminescent material; ηout is the light output efficiency. Without considering the light extraction coupling effect and the special structure that enhances the light output, it is generally believed that the light output efficiency is 20-30%.

[0008] From the above calculation formula, it can be seen that carbon dot materials with high luminous efficiency are a basic condition for preparing high-efficiency CDLEDs.

[0009] In summary, the development of high-efficiency and stable CDLED devices is of certain importance, and the light-emitting layer material plays a dominant role in CDLED devices, so the development and research of excellent CDs is very important. Summary of the invention

[0010] In order to solve the above technical problems, the present invention proposes a light emitting diode based on boron, nitrogen and fluorine co-doped carbon dots and a preparation method thereof.

[0011] To achieve the above object, the present invention provides the following technical solutions:

[0012] The technical solution of the present invention:

[0013] One of the technical solutions of the present invention:

[0014] A light-emitting diode based on boron-nitrogen-fluorine co-doped carbon dots, using ITO as a substrate, and comprising, from the substrate upward:

[0015] Hole injection layer formed by PEDOT:PSS solution;

[0016] A hole transport layer formed of TFB (poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-(4,4′-(N-(4-sec-butylphenyl)diphenylamine)]);

[0017] The light-emitting layer is formed with BNF-CDs as the guest material and PVK (poly(9-vinylcarbazole)) as the host material;

[0018] The electron transport layer formed by TPBi;

[0019] LiF forms the electron injection layer and the Al electrode;

[0020] The preparation process of BNF-CDs is as follows: in an organic solvent, 4-fluorophenylboric acid is used as a first precursor, and m-phenylenediamine is used as a second precursor, and the BNF-CDs are prepared by a solvothermal reaction.

[0021] Preferably, the usage ratio of 4-fluorophenylboric acid, m-phenylenediamine and organic solvent is (0.56-1.56) g: (0.5-0.8) g: (15-20) mL.

[0022] Preferably, the organic solvent includes methanol, anhydrous ethanol, isopropanol, toluene, tetrahydrofuran or N,N-dimethylformamide; more preferably anhydrous ethanol.

[0023] Preferably, the solvent thermal reaction conditions are: heating at 180-220° C. for 360-720 min.

[0024] Preferably, in terms of mass ratio, BNF-CDs:PVK in the light-emitting layer is equal to (0.3-2):(8-9.7).

[0025] Preferably, the thickness of the electron transport layer is 40-100 nm; the thickness of the electron injection layer is 0.5-5 nm; and the thickness of the aluminum electrode is 80-150 nm.

[0026] The second technical solution of the present invention:

[0027] The method for preparing the light-emitting diode based on boron-nitrogen-fluorine co-doped carbon dots comprises the following steps:

[0028] 1) 4-fluorophenylboric acid, m-phenylenediamine and an organic solvent are mixed, and ultrasound, solvent thermal reaction, cooling, separation and purification, rotary evaporation and drying are performed in sequence to obtain blue fluorescent carbon dot powder BNF-CDs;

[0029] 2) using the BNF-CDs as a guest material, poly (9-vinyl carbazole) (PVK) as a host material, and o-dichlorobenzene as a solvent to prepare a light-emitting layer mixed solution;

[0030] 3) treating the ITO substrate with ultrasound and ozone and placing it in a nitrogen environment for standby use;

[0031] 4) spin coating PEDOT:PSS solution, poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine)] and a light-emitting layer mixed solution on the treated ITO substrate in sequence;

[0032] Annealing treatment was performed after each spin coating;

[0033] 5) In a vacuum environment filled with nitrogen, an electron transport layer, an electron injection layer and an Al electrode are sequentially prepared by a thermal deposition method.

[0034] Preferably, the parameters in the ultrasonic process in step 1) are: ultrasonic temperature 30-60°C, time 30-60min.

[0035] Preferably, in step 2), the usage ratio of BNF-CDs, poly (9-vinyl carbazole) (PVK) and o-dichlorobenzene is (0.3-2) mg: (9.7-8) mg: (1-10) mL.

[0036] Preferably, the rotation speed of the spin coating of the PEDOT:PSS solution is 4000-6000r / 30-60s (meaning that it reaches 4000r within 30s, or reaches 6000r within 60s, and the spin coating is carried out quickly when the rotation speed is reached);

[0037] The rotation speed of spin coating the luminescent layer mixed solution is 2000-5000r / 30-60s.

[0038] Preferably, the conditions in the annealing process are: annealing at 100-150° C. for 15-30 min.

[0039] Preferably, the vacuum degree in the vacuum environment is 10 -5 Pa.

[0040] Compared with the prior art, the present invention has the following advantages and technical effects:

[0041] The invention uses 4-fluorophenylboric acid as a first precursor and m-phenylenediamine as a second precursor to prepare a blue fluorescent carbon dot powder with a fluorescence quantum yield of up to 88.41% and an emission wavelength of 430 nm. Then, the BNF-CDs are used as a guest material, poly 9-vinylcarbazole (PVK) is used as a main material, and o-dichlorobenzene is used as a solvent to prepare a luminescent layer mixed solution. The mixed solution is used as a luminescent layer raw material to prepare a high-efficiency light-emitting diode with good structural stability based on boron-nitrogen-fluorine co-doped carbon dots. The device EQE efficiency reaches 4.98%, which is a CLED with higher device efficiency among the current carbon dot-based light-emitting diodes. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0043] Figure 1 Schematic diagram of the preparation of BNF-CDs in Example 1 of the present invention;

[0044] Figure 2 This is a morphology characterization diagram of BNF-CDs prepared in Example 1 of the present invention;

[0045] Among them, a) is a transmission electron microscope (TEM) image (scale bar 20 nm); b) is a high-resolution transmission electron microscope (HRTEM) image (scale bar 2 nm), corresponding to a lattice spacing of 0.21 nm; c) is a statistical carbon dot size distribution;

[0046] Figure 3 This is the XRD spectrum of BNF-CDs prepared in Example 1 of the present invention;

[0047] Figure 4 This is the Raman spectrum of BNF-CDs prepared in Example 1 of the present invention;

[0048] Figure 5 This is the Fourier infrared spectrum of the BNF-CDs prepared in Example 1 of the present invention;

[0049] Figure 6It is the XPS spectrum of BNF-CDs prepared in Example 1 of the present invention; wherein b, c, d, e, and f are high-resolution XPS spectra of C1s, N 1s, O 1s, B 1s, and F 1s of BNF-CQD, respectively; a is the overall XPS spectrum;

[0050] Figure 7 This is the photophysical characterization spectrum of BNF-CDs prepared in Example 1 of the present invention;

[0051] Among them, a) is the ultraviolet absorption spectrum and luminescence spectrum of BNF-CDs; b) is the photoluminescence fluorescence quantum yield of BNF-CDs under different precursor molar ratio reactions; c) is the fluorescence spectrum of BNF-CDs under different polar solvents; d) is the low-temperature fluorescence spectrum and low-temperature phosphorescence spectrum of BNF-CDs; e) is the fluorescence decay curve of BNF-CDs, and f) is the phosphorescence decay curve of BNF-CDs;

[0052] Figure 8 The emission spectra of BNF-CDs prepared in Example 1 of the present invention in solvents of different polarities;

[0053] Among them, a) is Toluene; b) is THF; c) is DMF; d) is Ethanol; e) is isopropanol; f) is Methanol;

[0054] Fig. 9 The ultraviolet absorption spectrum and cyclic voltammetry curve of BNF-CDs prepared in Example 1 of the present invention;

[0055] Among them, a) is the UV absorption spectrum; b) is the cyclic voltammetry curve of BNF-CDs in (Bu)4NPF6 and ferrocene;

[0056] Fig.10 The structure and performance of the boron-nitrogen-fluorine co-doped carbon dot LED prepared in Example 1 of the present invention;

[0057] Among them, a) is the illustrated structure; b) is the energy level diagram; c) is the electroluminescence spectrum at different thicknesses of the electron transport layer; d) is the external quantum efficiency-brightness curve of the LED device. DETAILED DESCRIPTION

[0058] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0059] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0060] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0061] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0062] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0063] A method for preparing a light-emitting diode based on carbon dots comprises the following steps: using 4-fluorophenylboric acid as a first precursor and m-phenylenediamine as a second precursor, reacting the precursors at different molar ratios to prepare a series of blue carbon dot fluorescent powders BNF-CDs; then using BNF-CDs with the highest fluorescence quantum yield as a guest material, poly-9-vinylcarbazole (PVK) as a main material, and o-dichlorobenzene as a solvent to prepare a light-emitting layer mixed solution, which is used as a light-emitting layer raw material to prepare a light-emitting diode based on BNF-CDs.

[0064] The specific steps include:

[0065] 1) 4-fluorophenylboric acid, m-phenylenediamine and ethanol are mixed, wherein the ratio of 4-fluorophenylboric acid, m-phenylenediamine and ethanol is (0.56-1.56) g: (0.5-0.8) g: (15-20) mL; then, the mixture is ultrasonically dissolved at 30-60° C. for 30-60 min, and then transferred to an autoclave, reacted in a muffle furnace at a reaction temperature of 180° C. for 360 min, cooled to room temperature, separated and purified by column chromatography using ethyl acetate and petroleum ether as eluents to obtain a blue carbon dot solution, and then subjected to rotary evaporation and vacuum drying to finally obtain a blue carbon dot fluorescent powder BNF-CDs;

[0066] 2) using BNF-CDs as a guest material, poly (9-vinyl carbazole) (PVK) as a host material, and o-dichlorobenzene as a solvent, and the amount ratio of BNF-CDs, poly (9-vinyl carbazole) (PVK) and o-dichlorobenzene is (0.3-2) mg: (8-9.7) mg: (5-10) mL, to prepare a light-emitting layer mixed solution;

[0067] 3) Use a sponge dipped in Decon-90 cleaning solution to clean the ITO (indium tin oxide film, commonly known as ITO) glass surface until the water droplets on the surface are no longer hanging on the glass, and then use acetone, anhydrous ethanol and deionized water for ultrasonic cleaning at 70-80°C for 10-30 minutes respectively, and then use nitrogen to blow away the water stains on the ITO surface; then put it in an oven and dry it at 100-120°C for 2-4 hours, and finally ozone treat it for 20-60 minutes, and transfer it to a spin coating glove box filled with nitrogen;

[0068] 4) Spin coating a PEDOT:PSS (alias: poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid copolymer solution) solution onto the treated ITO substrate surface at a rotation speed of 3000-5500 r / 20s to form a film, and annealing at 100-150°C for 15-30min to form a PEDOT:PSS film; spin coating poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine)] onto the hole injection layer at a rotation speed of 3000-5000 r / 30s, and annealing at 150°C for 30min to obtain a hole transport layer;

[0069] 5) Spin-coating the light-emitting layer mixed solution prepared in step 2) onto the hole transport layer at a speed of 2000-5000r / 30-60s, annealing at 100-150°C for 15-30min, and preparing the electron transport layer TPBi, the electron injection layer LiF and the aluminum electrode by thermal deposition in a vacuum environment filled with nitrogen, with a vacuum degree of 10 -5Pa; the thickness of the electron transport layer is 40-100nm, the thickness of the electron injection layer is 0.5-5nm, and the thickness of the aluminum electrode is 80-150nm, thereby preparing a light-emitting diode based on boron, nitrogen and fluorine co-doped carbon dots.

[0070] The present invention also provides a method for preparing a light-emitting diode based on boron, nitrogen and fluorine co-doped carbon dots, and a light-emitting diode based on boron, nitrogen and fluorine co-doped carbon dots is prepared.

[0071] Example 1

[0072] A method for preparing a light-emitting diode based on boron-nitrogen-fluorine co-doped carbon dots, the steps are as follows:

[0073] 1) 0.8 g of 4-fluorophenylboric acid (F-Ph-B(OH)2) and 0.5 g of m-phenylenediamine (m-PDA) were mixed, 15 mL of anhydrous ethanol was added, and the mixture was ultrasonically dissolved at 60°C for 50 min, then transferred to an autoclave, and reacted in a muffle furnace at a reaction temperature of 180°C for 360 min. The mixture was cooled to room temperature, and ethyl acetate and petroleum ether were used as eluents. The blue carbon dot solution was separated and purified by column chromatography, and finally the blue carbon dot fluorescent powder BNF-CDs was obtained by rotary evaporation and vacuum drying (the specific process of rotary evaporation and vacuum drying is as follows: rotary evaporation is carried out by using a Dalong RE100pro rotary evaporator purchased on the market, vacuuming the carbon dots at 80°C with a vacuum pump, and then the carbon dots are dried by vacuum drying in an oven);

[0074] 2) Weigh 0.6 mg / 19.4 mg of BNF-CDs and poly (9-vinyl carbazole) (PVK) respectively, use 5 mL of o-dichlorobenzene as solvent, and prepare a mixed solution of the device light-emitting layer with a mass concentration of BNF-CDs of 3% (where 3% is obtained by dividing the total mass of carbon dots by the mass of carbon dots themselves plus PVK);

[0075] 3) Use a special soft sponge to dip into Decon-90 cleaning solution and rub the ITO (indium tin oxide film, commonly known as ITO) glass surface until the surface water droplets are no longer hanging on the glass surface. At 50°C, use acetone, anhydrous ethanol and deionized water for ultrasonic washing for 30 minutes respectively, and then use nitrogen to flush the water droplets on the ITO surface; then put it in an oven and dry it at 120°C for 2 hours, and finally ozone treat it for 30 minutes, and transfer it to a spin coating glove box filled with nitrogen for use;

[0076] 4) Spin-coating a PEDOT:PSS (alias: poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid) solution onto the treated ITO substrate surface at a speed of 5000 r / 20s to form a film, and annealing it at 150°C on a heating table for 20 min to form a PEDOT:PSS film; continue to spin-coat poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine)] onto the hole injection layer at a speed of 4000 r / 30s, and annealing it at 150°C for 30 min to form a hole transport layer;

[0077] 5) Spin-coating the light-emitting layer mixed solution prepared in step 2) onto the hole transport layer at a speed of 2500 r / 50 s, annealing at 150° C. for 20 min on a constant temperature heating table, and transferring to a vacuum evaporation chamber filled with nitrogen for use;

[0078] 6) In vacuum environment 10 -5 Pa, a 60nm electron transport layer TPBi, a 2nm electron injection layer LiF and a 90nm aluminum electrode were prepared by thermal deposition to prepare a light-emitting diode based on boron-nitrogen-fluorine co-doped carbon dots.

[0079] Example 2

[0080] Same as Example 1, except that in step 6), the thickness of the electron transport layer TPBi is 50 nm.

[0081] Example 3

[0082] Same as Example 2, except that, in step 6), the thickness of the electron transport layer TPBi is 40 nm.

[0083] Test Example 1

[0084] 1. Synthesis, preparation and purification of BNF-CDs

[0085] Figure 1The preparation schematic diagram of BNF-CDs in Example 1 of the present invention. 4-fluorophenylboric acid and m-phenylenediamine are selected as precursors for synthesizing carbon dots, ethanol is used as a solvent, and then carbon dots are prepared by a solvent thermal method. The synthesized carbon dots are separated and purified by column chromatography to obtain blue carbon dots, which are named BNF-CDs. 4-fluorophenylboric acid can be used as a very good carbon source because its carbon content is relatively high. Since the benzene ring of 4-fluorophenylboric acid also contains a boric acid group, it can also be used as a good boron source to retain the boron atom on CDs, thereby providing more reactive sites. Since there is also a strong electron-pulling effect of fluorine atoms on 4-fluorophenylboric acid, the luminescence of carbon dots may be enhanced. In addition, 4-fluorophenylboric acid also contains a benzene ring, which further enhances the conjugation degree of CDs and increases the rigidity of the molecule. Greater rigidity can reduce the vibration of polycyclic aromatic rings, so that the excitation energy cannot be easily released in the form of heat due to vibration. In addition, higher structural stability is also conducive to increasing the coplanarity of the molecule and increasing the conjugation of the π electrons in the carbon core, thereby reducing the absorption energy required for electron transitions, reducing the possibility of non-radiative transitions, and being more conducive to the generation of fluorescence. Since strong covalent bonds (BC, CN, CF, etc.) and hydrogen bond networks are also formed in CDs, the rotation of the CDs chromophore can be effectively restricted, thereby inhibiting the non-radiative recombination of triplet excitons, which is conducive to protecting the excited triplet excitons from quenching, promoting the phosphorescent emission of CDs, and further improving the external quantum efficiency (EQE) of the device.

[0086] 2. Morphology of BNF-CDs

[0087] Figure 2 This is a morphology characterization diagram of BNF-CDs prepared in Example 1 of the present invention; Figure 2 (a) is a transmission electron microscopy (TEM) image of BNF-CDs, showing that the carbon dots are evenly dispersed with an average size of 4.20 nm; Figure 2 (b) is a high-resolution transmission electron microscopy (HRTEM) image of BNF-CDs, showing high crystallinity and a lattice spacing of 0.21 nm, corresponding to the (100) plane spacing of graphene along the

[001] direction, proving that the synthesized CDs are almost defect-free graphene crystal structures; Figure 2 (c) is the particle size distribution diagram of BNF-CDs.

[0088] 3. Structural characteristics of BNF-CDs

[0089] 1) In order to further study the intrinsic characteristics of carbon dots, the present invention studies the structure of BNF-CDs.

[0090] Figure 3The XRD spectrum of BNF-CDs prepared in Example 1 of the present invention is shown in FIG. Figure 3 It can be seen that there is a strong and broad peak at about 28.3°, which is due to heteroatom doping or sp 3 The deformation caused by C defects leads to amorphous carbon on the (002) crystal plane, which is a typical feature of CDs.

[0091] Figure 4 This is the Raman spectrum of the BNF-CDs prepared in Example 1 of the present invention. As can be seen from the figure, at 1600cm -1 The CDs have an ordered G band at 1380 cm -1 There is a disordered D band at I G / I D The ratio is 2.80, indicating that the prepared BNF-CDs have a high crystallinity.

[0092] 2) In order to further study the relationship between the functional groups of carbon dots and the high fluorescence quantum yield, the present invention conducts an in-depth study on the surface functional groups of BNF-CDs.

[0093] Figure 5 This is the Fourier transform infrared spectrum of the BNF-CDs prepared in Example 1 of the present invention. The functional groups in the CDs are attributed and analyzed by FT-IR. By attributing each peak in the Fourier transform infrared spectrum, the internal structure of the BNF-CDs and the functional groups existing on the edge can be further studied. Figure 5 The spectrum of the raw material 4-fluorophenylboronic acid shows that the -1 、3000cm -1 、1670cm -1 and 1350cm -1 The characteristic absorption of can be attributed to the stretching vibration of OH, the stretching vibration of CH on the benzene ring, the stretching vibration of C=C and the stretching mode of CF bond. These functional groups can also be observed in BNF-CDs, but the position is shifted to 3350cm -1 、2900cm -1 、1650cm -1 and 1345cm -1 , which suggests that there may be other interactions in CDs that are different from the starting materials and also proves the successful synthesis of CDs.

[0094] There are strong electron-donating groups such as hydroxyl and amino groups on the surface of the precursor 4-fluorophenylboronic acid and m-phenylenediamine. The boronic acid groups on the precursor condense with the amino groups to form hydrogen bonds and BN covalent bonds. In addition, the F atoms on the benzene ring can also form hydrogen bonds with hydrogen atoms to construct the basic skeleton of the carbon dots to form a graphite structure, making the CDs more rigid, reducing the vibration of the polycyclic aromatic rings in the skeleton, and making it difficult for the excitation energy to be released in the form of heat due to vibration. The strong covalent bonds (BC, CN, CF, etc.) and hydrogen bond networks formed can effectively limit the rotation of the CDs chromophore, thereby inhibiting the non-radiative recombination of triplet excitons and protecting the excited triplet excitons from quenching. Under the joint action of these groups, the carbon dots finally have a higher fluorescence quantum yield.

[0095] 3) In order to confirm the valence and bonding information of B, C, N, O and F in the carbon dots, the present invention performs X-ray photoelectron spectroscopy (XPS) test on BNF-CDs, see Figure 6 af. In the XPS spectrum a, there are signal peaks of B1s (191.1eV), C1s (284.1eV), N 1s (400.0eV), O 1s (532.6eV) and F1s (678.5eV), among which the content of B element is 2.63% and the content of F element is 0.42%. XPS confirmed the FTIR data, indicating that BNF-CDs are composed of only B, C, N, O and F. This shows that there are no metal or other non-metallic impurities in the elemental composition of CDs. Compared with traditional OLED materials or QLED materials, the preparation of CDs is widely available, metal-free, low-cost and green.

[0096] The high-resolution B1s, C1s, N 1s, O 1s and F1s spectra of CDs are shown in Figure 2. Figure 6 The high-resolution XPS spectrum of B 1s ( Figure 6 (e) shows three peaks at 190.5 and 187.0 eV, which can be attributed to CBN and BC. The high-resolution XPS spectrum of C 1s ( Figure 6 (b) shows three different forms of peaks: CO / CN (286.4 eV), CC / C=C (284.8 eV) and CB (283.5 eV). High-resolution XPS spectrum of N 1s ( Figure 6 c) There are five peaks at 400.8, 400.0, 398.6, 399.1 and 398.0 eV, corresponding to NH, graphite N, pyridine N, NC and NB, respectively. High-resolution XPS spectrum of O 1s spectrum ( Figure 6(d) shows the presence of O=C bonds (532.1 eV) and OH bonds (533.8 eV) in CDs. High-resolution XPS spectrum of F 1s spectrum ( Figure 6 Middle f) shows the presence of CF bonds (686.7 eV) in CDs.

[0097] 4. Optical properties of BNF-CDs

[0098] In order to further explore the relationship between the high fluorescence quantum yield of CDs and the photoluminescence mechanism, the present invention studies and discusses the optical properties of the prepared carbon dots.

[0099] Figure 7 The photophysical characterization spectra of BNF-CDs prepared under different conditions. Figure 7 a) is the UV-visible absorption spectrum and fluorescence spectrum of BNF-CDs prepared in Example 1 of the present invention. From the UV-visible absorption spectrum of BNF-CDs, it can be seen that the UV absorption peak at around 300nm is the π-π * Electronic transition, showing a strong absorption band around 350-450nm, corresponding to n-π in CDs * Characteristic absorption peak generated by transition. From the fluorescence spectrum in Figure a), it can be seen that the fluorescence spectrum of BNF-CDs presents a single peak emission with an emission peak at 430nm. And it can be found that the peak has a downward swing phenomenon, resulting in a wide half-peak width of about 60nm.

[0100] Figure 7 b) is the photoluminescence quantum yield of BNF-CDs. It can be seen from the figure that at the optimal precursor ratio of 11:1, the photoluminescence quantum yield (PLQY) of BNF-CDs is 89.65%. Figure 7 b) and c) control variables. For example, in b), except for the different molar ratio, the other parameters are the same as those for preparing BNF-CDs in Example 1; in c), except for the different solvent types, the other parameters are the same as those for preparing BNF-CDs in Example 1.

[0101] Figure 7Figure c) shows the fluorescence spectra of BNF-CDs in solvents of different polarities. The normalized photoluminescence curves of BNF-CDs in aprotic solvents of different polarities, including n-hexane (n-Hexane), toluene (Toluene), dichloromethane (Dichloromethane, DCM), tetrahydrofuran (Tetrahydrofuran, THF), acetonitrile (Acetonitrile, ACN) and N,N-dimethylformamide (N,N-Dimethylformamide, DMF), show that the center of the photoluminescence emission position of CDs changes slightly with the change of the polarity of the aprotic solvent, which reflects that CDs are less sensitive to the environment, that is, the passivation structure on the surface of CDs plays a good protective role, making CDs more advantageous in the application of LED devices.

[0102] Figure 7 Figure d) shows the low-temperature fluorescence and phosphorescence spectra of BNF-CDs. From the low-temperature fluorescence spectrum curve, it can be seen that there is a maximum emission peak at 430nm. Therefore, the photoluminescence mechanism of CDs may come from the center of the carbon core.

[0103] Figure 7 e) in the figure is the fluorescence decay lifetime curve of BNF-CDs. It can be seen from the figure that the decay lifetime presents a single exponential decay (see Table 1 for the results).

[0104] Figure 7 Figure f) is the phosphorescence decay lifetime curve of BNF-CDs. It can be seen from the figure that the decay lifetime presents a multi-exponential decay (see Table 1 for the results). The existence of multiple lifetimes also indicates that the emission of CDs comes from multiple recombination centers in the carbon core.

[0105] Table 1 Fluorescence lifetime and phosphorescence lifetime of BNF-CDs

[0106]

[0107] Furthermore, the effects of solvents on the optical properties of CDs and the photoluminescence mechanism of CDs were investigated. Protic solvents of different polarities, such as methanol, ethanol, isopropanol, and aprotic solvents, such as toluene, tetrahydrofuran (THF), and N,N-dimethylformamide (DMF), were used as solvents, and different excitation wavelengths were used to excite BNF-CDs in solvents of different polarities.

[0108] Figure 8 The emission spectra of BNF-CDs prepared in Example 1 of the present invention in different polar solvents are shown in FIG. Figure 8It can be seen that under different excitation wavelengths, the center of the photoluminescence emission position of BNF-CDs is basically unaffected, which proves the excitation wavelength independence of CDs. In addition, in aprotic solvents such as toluene, tetrahydrofuran and N,N-dimethylformamide, the fluorescence peak of BNF-CDs is dominated by 430nm, while in protic solvents such as ethanol, methanol and isopropanol, the fluorescence peak of BNF-CDs is dominated by 530nm. This may be due to the fact that the formed hydrogen bond network can effectively restrict the rotation of the CDs chromophore, thereby inhibiting the non-radiative recombination of triplet excitons and protecting the excited triplet excitons from quenching, thereby enhancing the fluorescence emission.

[0109] Combined with the conclusions obtained, first of all, BNF-CDs have the typical characteristics of carbon core emission: (i) single exponential decay; (ii) excitation wavelength independence. These all prove that the photoluminescence behavior is emitted inside the carbon core, proving that its photoluminescence mechanism is carbon core state emission. Therefore, using BNF-CDs with high fluorescence emission to prepare electroluminescent diodes is expected to further improve device efficiency.

[0110] The HOMO and LUMO energy levels of BNF-CDs were then estimated by cyclic voltammetry.

[0111] Fig. 9 The UV absorption spectrum and cyclic voltammetry curve of BNF-CDs prepared in Example 1 of the present invention are shown in Figure 1. The present invention uses a glassy carbon electrode as the working electrode, a platinum sheet as the counter electrode (auxiliary electrode), and an Ag / Ag + The cyclic voltammetry (CV) curve was drawn using a standard three-electrode system composed of a reference electrode. The CV curve was scanned in acetonitrile containing 0.1 M tetrabutylammonium, ammonium hexafluorophosphate ((Bu)4NPF6) was used as the electrolyte, and ferrocene was used to calibrate the potential. According to the following formula:

[0112] E HOMO =-[E ox +E(Fc / Fc + )+4.8]

[0113] E g =1240 / λ onset

[0114] E LUMO =E HOMO +E g

[0115] Among them, E HOMO is the highest molecular occupied orbital; E ox is the sample initial energy level; Fc / Fc + is the starting energy level of ferrocene; λ onsetis the starting absorption wavelength of UV-visible absorption; E g is the energy gap; E LUMO is the lowest molecular occupied orbital.

[0116] According to the results of cyclic voltammetry, the Eg of the BNF-CDs prepared by the present invention is 3.01eV, the HOMO energy level is -6.12eV, and the LUMO energy level is -3.11eV. The energy level of BNF-CDs is close to that of the main material poly(9-vinylcarbazole) (PVK).

[0117] 5. CDLED device of BNF-CDs

[0118] BNF-CDs have a higher fluorescence quantum yield, which is more conducive to the development of its application in LEDs and promotes the development of a new generation of display technology. The device structure of the light-emitting diode prepared in Example 1 of the present invention adopts a simple and reasonable design, with poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) (PEDOT:PSS) as a hole injection layer, poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine)] (TFB) as a hole transport layer, and the light-emitting layer adopts a host-guest doping system. The light-emitting layer uses BNF-CDs as a guest material and poly-9-vinylcarbazole (PVK) as a host material. 1,3,5-Tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi) is used as an electron transport layer, and LiF / Al is used as a double-layer cathode, such as Fig.10 a) and Fig.10 As shown in b).

[0119] In the present invention, BNF-CDs is used as the guest material of the light-emitting layer, and the thickness of the electron transport layer TPBi is adjusted under the device light-emitting layer doping concentration of 3%. Compared with Example 1, the only difference is step 6: the thickness of TPBi is 50nm (Example 2), and the thickness of TPBi is 40nm (Example 3). The detailed data of the three devices are shown in Table 2. Fig.10 c) and Fig.10 As shown in d), the light emission position of CDLEDs with different thicknesses of the electron transport layer TPBi is around 440nm, with no obvious effect. As the thickness increases, the device efficiency EQE value of CDLED increases from 0.78% to 2.66% and 4.98%. Among them, the CDLED device with a TPBi thickness of 50nm has the highest efficiency.

[0120] Table 2 CDLED performance data results of BNF-CDs

[0121]

[0122] The results show that by regulating the thickness of the electron transport layer TPBi so that the carrier injection and transport in the device are in a balanced state, the device efficiency can be improved; and when the thickness of the electron transport layer TPBi reaches 50nm, the EQE reaches a limit of 4.98%.

[0123] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A light-emitting diode based on boron-nitrogen-fluorine co-doped carbon dots, using ITO as a substrate, characterized in that: From the base upwards they include: Hole injection layer formed by PEDOT:PSS; A hole transport layer formed of poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine)]; The light-emitting layer is formed with BNF-CDs as the guest material and PVK as the host material; The electron transport layer formed by TPBi; The electron injection layer formed by LiF and the Al electrode; The preparation process of BNF-CDs is as follows: in an organic solvent, 4-fluorophenylboric acid is used as a first precursor, and m-phenylenediamine is used as a second precursor, and the BNF-CDs are prepared by a solvothermal reaction.

2. A light-emitting diode based on boron-nitrogen-fluorine co-doped carbon dots according to claim 1, characterized in that: The usage ratio of the 4-fluorophenylboric acid, m-phenylenediamine and the organic solvent is (0.56-1.56) g: (0.5-0.8) g: (15-20) mL.

3. A light-emitting diode based on boron-nitrogen-fluorine co-doped carbon dots according to claim 1, characterized in that: The solvent thermal reaction conditions are: heating at 180-220° C. for 360-720 min.

4. The light-emitting diode based on boron-nitrogen-fluorine co-doped carbon dots according to claim 1, characterized in that: In terms of mass ratio, BNF-CDs:PVK in the light-emitting layer is equal to (0.3-2):(8-9.7).

5. The light-emitting diode based on boron-nitrogen-fluorine co-doped carbon dots according to claim 1, characterized in that: The thickness of the electron transport layer is 40-100 nm.

6. A method for preparing a light-emitting diode based on boron-nitrogen-fluorine co-doped carbon dots, characterized in that: The following steps are involved: 1) 4-fluorophenylboric acid, m-phenylenediamine and an organic solvent are mixed, and ultrasound, solvent thermal reaction, cooling, separation and purification, rotary evaporation and drying are performed in sequence to obtain blue fluorescent carbon dot powder BNF-CDs; 2) using the BNF-CDs as a guest material, PVK as a host material, and o-dichlorobenzene as a solvent to prepare a light-emitting layer mixed solution; 3) treating the ITO substrate with ultrasound and ozone and placing it in a nitrogen environment for standby use; 4) spin coating PEDOT:PSS solution, poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine)] and a light-emitting layer mixed solution on the treated ITO substrate in sequence; Annealing treatment was performed after each spin coating; 5) In a vacuum environment filled with nitrogen, an electron transport layer, an electron injection layer and an Al electrode are sequentially prepared by a thermal deposition method to prepare a light-emitting diode based on boron-nitrogen-fluorine co-doped carbon dots as described in any one of claims 1 to 5.

7. The method for preparing a light-emitting diode based on boron-nitrogen-fluorine co-doped carbon dots according to claim 6, characterized in that: The parameters in the ultrasonic process in step 1) are: ultrasonic temperature 30-60°C, time 30-60min.

8. The method for preparing a light-emitting diode based on boron-nitrogen-fluorine co-doped carbon dots according to claim 6, characterized in that: Step 4) Spin coating the PEDOT:PSS solution at a speed of 4000-6000 r / 30-60 s; The rotation speed of spin coating the light-emitting layer mixed solution is 2000-5000r / 30-60s.

9. The method for preparing a light-emitting diode based on boron-nitrogen-fluorine co-doped carbon dots according to claim 6, characterized in that: Step 4) The conditions in the annealing process are: annealing at 100-150° C. for 15-30 min.

10. The method for preparing a light-emitting diode based on boron-nitrogen-fluorine co-doped carbon dots according to claim 6, characterized in that: Step 5) The vacuum degree in the vacuum environment is 10 -5 Pa.